Intervensi Perilaku Sadar Bahaya Rokok Melalui Humor dan Rational Based Message Appeals - Swastikawara, Sinta; Laturrakhmi, Yun Fitrahyati; Oktaviani, Fitri Hariana (Faculty of Communications Science, Dr. Soetomo University, 2018)
Through a participatory action research study, this study identifies and analyses the associations and symbols attached by adolescents at school age in target schools, identifies strategies and message appeals based on the associations and embedded symbols so that it is appropriately used for preventive efforts of smoking behaviours and. Based on the results of the study can be concluded that there are two perspectives in associating cigarettes, first is the symbol of masculinity and flexibility in associating, the second is associated with opium, and poison. Further intervention can be done by presenting humour based appeals at the group level and rational based message appeals at the individual level. In the context of health communication, this research has shown how Social Cognitive Theory is used in the study of promotion of health by emphasising the design of fear-based appeals.